Here and there : cross-linguistic studies on deixis and demonstration - Weissenborn, Jürgen; Klein, Wolfgang, 1946 February 3- (Pragmatics & beyond, 1982)
Deixis - the rooting of utterances in the speech situation - is one of the most salient universals of natural language. The ways in which different languages link utterances to pragmatic factors such as speech time, speech place, and speech participants show a rich variation. This makes deixis a particular fruitful domain for the study of universals, language comparison, and the relationship between language and reality. This volume presents and discusses deictic systems of both Indo-European and non-Indo-European languages, including Russian, Czech, Spanish, German (standard and dialect), Hun.